The History of Term «Museology» Origin - Dmytro Kepin (Вісник Київського національного університету культури і мистецтв. Серія: Музеєзнавство і пам’яткознавство, 2018)
The article examines the rise of the term "Museology" in historical context in the countries of Europe.